ANALISIS PERLINDUNGAN HUKUM TERHADAP MASYARAKAT TELUK JAKARTA UTARA AKIBAT REKLAMASI PULAU G (STUDI PUTUSAN MARI NOMOR: 92K/TUN/LH/2017 TENTANG PERIZINAN REKLAMASI) - KARINA ISMI SABARINA SEMBIRING (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Syafruddin Kalo, SH, Mhum2.  Prof. Dr. Muhammad Yamin, SH, MS, CN3.  Prof. Dr. Hasim Purba, SH, MHum Reclamation is the process of making new land from the bottom of the sea or river. The land that is reclaimed is called reclamation or landfill. In accordance with the Law, reclamation is defined as the activity that is done to increase the use of the land resources observed from enviromental and economical social views by means of land encirclement and drainage. In case the Government of DKI Jakarta Province wants to carry out reclamation of G Island to PT. Muara Wisesa, they have to prevent the rights of the people at Teluk Jakarta Utara form being violated. They also have to meet all the requirements for the license either from procedural or substancial licenses. Keywords: Reclamation, G Island, People at Teluk Jakarta Utara